Evaluation of the European legislative framework in assessing the vulnerability of surface and groundwater bodies to road runoff - Martins, Tiago N.; Leitão, Teresa E.; Lundy, Lian (International Conference “Environmental Engineering”, 2020)
This article presents an overview of the current European practices with regards to protecting surface water and groundwater bodies, in what concerns the application of legislation to protect water resources and to evaluate the vulnerability of water bodies to traffic related activities. This is achieved through the application of the EU Water Framework Directive and all Directives containing procedures to identify pressures affecting the state of water and environment, and the establishment of measures to ensure that all surface water and groundwater bodies achieve good status. A flowchart has been constructed to assist the assessment of the environmental legal constraints related to a road project. A combination of layers was integrated in GIS environment to address legislative needs and constraints, as well as the need to implement a risk assessment analysis of road runoff impact to surface and groundwater bodies.